Effect of CO2 on the Hydration of Aluminate Cement Under Conditions of Burning Reservoir in Heavy Oil Thermal Recovery - Wu, Guangai; Wu, Zhiqiang; Xing, Xuesong; Cai, Jingxuan; Cheng, Xiaowei (Frontiers in Materials, 2022)
Under conditions of heavy oil thermal recovery, cement sheaths often suffer high-temperature performance degradation and CO2 corrosion. The performance of Class G oil well cement commonly used for cementing, deteriorates significantly at high temperatures and in CO2 environments, which can easily cause accidents. By contrast aluminate cement (CAC), at the same time, has good high-temperature resistance and corrosion resistance. Therefore, this study explored the mechanical properties and permeability of CAC with a high-temperature stabiliser cement slurry system (C1), pure CAC slurry system (C2) and Portland cement with sand cement slurry system (C3) before and after corrosion at 50, 300, 400, 500, and 600°C. The micromorphology, hydration products and pore structure of the cement paste before and after corrosion were analyzed using scanning electron microscopy, X-ray diffraction, thermogravimetry and nitrogen adsorption specific surface area and pore diameter analysis; additionally, the hydration mechanism of CAC under high temperatures and in CO2 environments was explored. The results show that the degree of degradation of the mechanical properties of C1 cement slurry system at high temperatures and under CO2 corrosive environments is significantly lower than that of the C3 cement slurry system. At a curing high temperature of 400°C, the maximum strength of the C1 cement paste reached 36.39 ± 0.37 MPa. The addition of a high-temperature stabiliser improved the mechanical properties of CAC at low temperatures, reduced the formation of C3ASH4 in the cement paste at high temperatures, and improved the strength of the cement paste after high-temperature curing. Compared with the C3 cement slurry system, the C1 cement slurry system had better high-temperature resistance and corrosion resistance and was more suitable for application under conditions of a burning reservoir in heavy oil thermal recovery.